Políticas afirmativas na Universidade Federal do Ceará: Desafios e conquistas da educação diferenciada no curso de Magistério Indígena Tremembé Superior- MITS - Ribeiro, Selma Helena Marcos (2013)
This research has as main objective to investigate, according to the point of view of the graduate students, the occurrences concerning the challenges and achievements on the study programme “Curso de Magistério Indígena Tremembé Superior” (MIts), offered by the Universidade Federal do Ceará, in the native Indian villages in Almofala Itarema, Ceará ; as an affirmative statement action policy directed towards the native Brazilian indians. The theoretical foundation comprises conceptual aspects of affirmative statement actions policies ,intercultural and differentiated education related to the native Brazilian Indians and, by extension, national policy foundation on higher education. Also it describes general characteristics of the ethnic group Tremembé and the graduation Course (Mits). This research can be characterized as having an empirical nature type of research, also descriptive with a qualitative approach. As for the technical method of procedure for collecting data, were used both bibliographic and documental resources as well as case report method. The participants of the research were graduate students from “Mits” concluding in 2013, the course general coordinator, José Mendes Fonteles Filho and in addition, the leader of the Tremembés tribe,João Venâncio. The data, collected through interviews, revealed the following categories: Differentiated education, Challenges and Obstacles; Benefits; Protagonism. It could be concluded that one of the main challenges faced by MITS course was related to the its realization in the native indians village itself, in the sense of fulfill the Pedagogic Politic project, towards the reality of the Tremembés Indians and with autonomy. Regarding the achievements, it is remarkable the Tremembés instructors’ formation, able to act as educators,school managers and actual citizens conscious of their rights. As the most relevant point of the MITS, comes the Tremembés protagonism on the history of the differentiated education and specially on the higher education. On the other hand, it is as well remarkable the pioneerism of UFC in approving and developing the project, thus adding to its history the title of being the first higher education institution supporting a university course for native Indians , entirely given in natives Indians villages in Itarema , Ceará.